The 'New' national development planning and global development goals: Processes and partnerships. (August 2019) - Chimhowu, Admos O.; Hulme, David; Munro, Lauchlan T.
Highlights: Over 130 countries have produced national development plans to show their priorities for achieving SDGs. Many of the plans are a product of national consensus processes although some are produced mainly technocratic elites. The five year (medium term) plan is the most popular although some countries have longer term visions documents. National Planning Commissions are back and play a lead role although Economic Ministries still dominate the process. A majority of national plans lack financing strategies a factor that can affect implementation and achievement of SDGs. Abstract: The number of countries with a national development plan has more than doubled, from about 62 in 2006 to 134 in 2018. More than 80 per cent of the global population now lives in a country with a national development plan of one form or another. This is a stunning recovery of a practice that had been discredited in the 1980s and 1990s as a relic of directed economies and state-led development. Several factors have fostered this re-emergence but from about 2015 the momentum for producing plans has accelerated, driven in part by a need to plan for the Sustainable Development Goals (SDGs). Based on an analysis of 107 national development plans, and drawing insights from 10 case study countries, this paper analyses 'new' national development planning and identifies the types and content of the plans, and their implications for the sustainable development agenda. The paper generates a typology of the new national plans, analyses their characteristics and explores the ways in which the new national development planning and the SDGs may interact. The study finds greater ownership and political control of the processes leading to plan production. It also finds that the plans vary in terms of the evidence used, the degree of internal consistency between different parts of the same plan, the process of developing the plan (inclusive or elite-driven), and the extent to which they are clear on how they will be financed. In contrast to 20th-century national development plans the new-generation plans are often underpinned by theories of collaborative rationality rather than by linear rationality. This new generation of national plans has been neglected by academic researchers and merits much greater examination, especially to understand the ways in which their implementation can enhance the achievement of the SDGs.